Innovación 10x en el sector Agropecuario de Colombia - Amaya, Javier Ricardo
We present the case study of an innovation process in a Colombian company, Inversiones El Fical (IEF). During 2018 and 2019, IEF developed ISMOC, a research and development project sponsored by SENNOVA to increase 10 times the production of Tilapia in a rural facility at El Playón, Santander. To that end, we detail the process, goals and results of the innovation programme. We start by describing the requirements’ capture for developing impactful innovation in the tilapia value chain. Then, we present the way pH, O2 and temperature sensor monitoring was interconnected with cloud services and introduce the real-time blowers automatic control deployed. Following, we introduce the technical and organisational findings/challenges that SMEs might face when adopting innovation practices. Finally, we highlight the success of the program and describe the required conditions to expand innovation programmes in the agricultural sector.